2023
DOI: 10.1088/1361-6463/acbce0
|View full text |Cite
|
Sign up to set email alerts
|

Ionization wave propagation of a surface dielectric barrier discharge with a flexible-structure plasma sheet

Abstract: Plasma sources based on flexible substrates are receiving attentions for their unique adaptability to irregular surfaces and large range of plasma coverage, which brings them irreplaceable advantages in the fields of material processing and biomedical treatment. Plenty studies have been carried out focusing on the application effects of these flexible plasma sources, while their surface discharge characteristics and mechanisms still lack revelation. In this work, a flexible plasma sheet with the structure of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Nevertheless, TTB is widely used to calculate the various types of gas discharges (streamers [33,34], glow discharges [35,36], sparks [37], DBD [38,39], corona discharges [40,41]), including in the near-electrode regions, where abnormally high electric fields and their gradients are. In this case, there is no opportunity to study the phenomena caused by the difference in longitudinal and transverse diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, TTB is widely used to calculate the various types of gas discharges (streamers [33,34], glow discharges [35,36], sparks [37], DBD [38,39], corona discharges [40,41]), including in the near-electrode regions, where abnormally high electric fields and their gradients are. In this case, there is no opportunity to study the phenomena caused by the difference in longitudinal and transverse diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The distinct plasma generation mechanisms of PD and ND lead to notable differences in the plasma behavior and the generation of active species. For examples, Lu et al [18] observed that in PD the luminous region of the plasma jet is mainly focused at the plasma bullet head, while in ND the entire channel of the plasma jet emits light. Sun et al [19] studied the propagation of surface ionization waves on curved gas-solid interfaces through experiments and simulations.…”
Section: Introductionmentioning
confidence: 99%